Targeting Myc Interacting Proteins as a Winding Path in Cancer Therapy - Zhou, Yihui; Gao, Xiaomeng; Yuan, Meng; Yang, Bo; He, Qiaojun; Cao, Ji (Frontiers in Pharmacology, 2021)
MYC, as a well-known oncogene, plays essential roles in promoting tumor occurrence, development, invasion and metastasis in many kinds of solid tumors and hematologic neoplasms. And proteins that directly interact with Myc have exerted a significant impact in the process of Myc-driven carcinogenesis. Apart from affecting the transcription of Myc target genes, Myc interaction proteins also regulate the stability of Myc through acetylation, methylation, phosphorylation and other post-translational modifications, as well as competitive combination with Myc. In this review, we summarize a series of Myc interacting proteins and recent advances in the related inhibitors, hoping that can provide new opportunities for Myc-driven cancer treatment.